Leading the high energy culture [ what the best CEOs do to create an atmosphere where employees flourish - Casullo, David (McGraw-Hill, 2012)
Using his own experience, research, and demonstrated results from the leadership development program that he developed while helping transform Raymour & Flanigan from a small regional company to a billion-dollar furniture retail giant, the author outlines the specific steps that let you discover and unlock the latent energy in your team